Ethnobotanical assessment of woody flora of district Kasur (Punjab), Pakistan - Arshad, Fahim; Waheed, Muhammad; Iqbal, Muhammad; Fatima, Kaniz; Fatima, Kaneez (Ethnobotany Research and Applications, 2020)
Abstract Background: An ethnobotanical survey of woody flora comprising of trees was conducted from district Kasur, Punjab, Pakistan. Materials and Methods: The data was collected by interviewing native people through a semi-structured questionnaire. Results: A total of 78 tree plant species belonging to 63 genera and 27 families were explored from the study area. The ethnobotanical results revealed that 21 species had medicinal importance, 11 species were used as fodder, 16 species as fuel wood, 10 species for making agriculture tools, 19 species in furniture, 33 species were ornamentals, fruits or flowers of 7 species were cooked as vegetable, 04 species were utilized as hedge, 6 species for shade purpose and 7 species had multifarious perspectives. The inhabitants of studied area utilized 21 tree species out of 78 against various ailments viz.; cough (33.3%), asthma (23.8%), diabetes (23.8%), sexual tonics (28.5%), liver problems (9.5%), skin disorders (23.8%), wounds healing (9.5%), blood purifier (9.5%), kidney problems (4.7%), piles (19%), digestive disorders (28.5%), jaundice (4.7%), fever and flu (28.5%), menstrual problems (9.5%) and toothache (14.2%). Conclusions: The ethnobotanical utilization trend observed was most prevalent amongst the rural communities of the studied area. Keywords: Ethnobotany, Woody flora, Indigenous knowledge, Kasur. خلاصہ: پس منظر: پنجاب ، پاکستان ، ضلع قصور میں درختوں پر مشتمل نباتاتی پودوں کا مطالعہ کیا گیا۔ مواد اور طریقے کار: یہ اعداد و شمار نیم ساختہ سوالنامے کے ذریعے مقامی لوگوں کے انٹرویو کےذریعے جمع کیے گئے- نتائج: علاقے سےمجموعی طور پر٦۳ نسلوں اور ۲۷ خاندانوں سےتعلق رکھنے والے ۷۸ درختوں کا مطالعہ کیا گیا۔ نباتاتی مطالعہ کے نتائج سے یہ بات سامنے آئی ہے کہ ۲۱ پودوں کو دواؤں کی اہمیت حاصل ہے ، ۱۱ پودوں کو چارہ کے طور پر استعمال کیا جاتا ہے ، ایندھن کی لکڑی کے طور پر ۱٦ پودوے ، زراعت کے اوزار بنانے کے لئے ۱۰ پودوے ، فرنیچر میں ۱۹پودوے ، ۳۳ پودوں کو زیبائش کے لئے ، ۰۷ پودوں کے پھول یا پھل کو سبزی کے طور پر پکایا گیا تھا ۰۴ پودوں کو رکاوٹ کے طور پر ، ۰٦ پودوں کو سایہ کے مقصد کے لئے اور ۰۷ پودوں کو متعدد نقطہ نظر سے استعمال کیا گیا تھا۔ زیرِ مطالعہ علاقے کے باشندوں نے ۷۸ میں سے ۲۱ درختوں کو مختلف بیماریوں میں استعمال کیا جیسا کہ؛ کھانسی (۳۔۳۳٪) ، دمہ (۸۔۲۳٪) ، ذیابیطس (۸۔۲۳٪) ، جنسی ٹانک (۵۔۲۸٪) ، جگر کے مسائل (۵۔۹٪) ، جلد کے امراض (۸۔۲۳٪) ، زخموں کی شفا (۵۔۹٪) ، بلڈ پیوریفائر (۵۔۹٪) ، گردے کی پریشانی (۷۔۴٪) ، بواسیر (۱۹٪) ، ہاضمے کی خرابی (۵۔۲۸٪) ، یرقان (۷۔۴٪) ، بخار اور فلو (۵۔۲۸٪) ، ماہواری کے مسائل (۵۔۹٪) اور دانت میں درد (۲۔۱۴٪) شامل ہیں۔ اخذ شدہ نتیجہ: مطالعہ شدہ علاقے کی دیہی برادریوں میں پودوں کے استعمال کا رجحان سب سے زیادہ پایا جاتا ہے۔ کلیدی الفاظ: ایتھنوبوٹنی ، ووڈی فلورا، دیسی علم ،قصور